2009
DOI: 10.1007/s12098-009-0007-3
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented villonodular synovitis of the elbow

Abstract: We present a 16 year old student with right elbow pigmentary villonodular synovitis. Clinical diagnosis, radiological features, MRI findings, biopsy results, management and follow up are discussed. MRI is the diagnostic modality of choice and assists the surgeon for a proper incision. Correlation of all the clinical aspects and the histologic features is usually required for definitive diagnosis. A complete surgical synovectomy provides the best chance for cure, but the goal of eradication of this benign proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Identification with additional synovitis diseases is necessary before diagnosis, including rheumatoid synovitis, gouty synovitis, infectious synovitis, pigmented villonodular synovitis, and synovial chondromatosis [10][11][12][13][14][15] . As the optimal detection of RBS, MRI findings are very typical.…”
Section: Discussionmentioning
confidence: 99%
“…Identification with additional synovitis diseases is necessary before diagnosis, including rheumatoid synovitis, gouty synovitis, infectious synovitis, pigmented villonodular synovitis, and synovial chondromatosis [10][11][12][13][14][15] . As the optimal detection of RBS, MRI findings are very typical.…”
Section: Discussionmentioning
confidence: 99%
“…MRI strongly supports the diagnosis of PVNS through the demonstration of areas of low- or iso-signal intensity on T1-and T2-weighted images, indicative of signal attenuation by the abnormal iron content in the hemosiderin within a thickened synovium (19,25). A number of studies have reported the MRI features of PVNS in the elbow joint (7,9,13,16,20). On T1-weighted images, the lesion demonstrates isointensity to muscle with small areas of low signal intensity, while T2-weighted images demonstrate mildly increased signal intensity in the lesion.…”
Section: Discussionmentioning
confidence: 99%